Influence of Progesterone Levels at AI and during Early Luteal Phase on Conception in Acyclic Sahiwal Cows Treated with Ovulation Synchronization Regimens - Paikra, Dilip Kumar; Awasthi, Manoj Kumar; Khan, Javed R; Parveen, Kaiser; Paikra, Dimpal; Sahu, Suryakant (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present experiment attempted to examine the influence of serum progesterone concentrations on conception rate in acyclic cows  that were treated with three variants of ovsynch protocol. Postpartum (> 90 days) acyclic Sahiwal cows (n=18) were divided into three  groups; each group consisted of six animals. Animals of group I were treated with modified ovsynch, group II animals with modified  heat-synch and those of group III were treated with modified select-synch regimens. FTAI was performed in animals of group I and group  II, whereas animals of group III were inseminated at detected estrus. Detection of conception was accomplished by ultrasonography on  day 35 post-AI and confirmed later by examination per rectum between days 50-60 post-AI. Based on pregnancy diagnosis the animals  were divided into conceived and non-conceived groups irrespective of treatment given to the animals. Blood samples were collected on  the day of AI, days 10 and 20 post-AI for estimation of serum estradiol, insulin and progesterone levels using RIA kits. Results revealed that  on the day of AI conceived animals had significantly higher serum estradiol concentrations (51.32±5.55 vs. 32.13±2.47 pg/mL, p ≤ 0.05)  and insulin concentrations (17.61±0.74 vs. 12.94±0.39 µIU/mL, p
Keywords: Acyclic, Conception, Estradiol, Insulin, Sahiwal cows, Supra-basal progesterone